Pengaruh Tingkat Pendapatan Kepala Keluarga terhadap Tingkat Pendidikan Anak Penerima Program Keluarga Harapan (PKH) di Desa Jombok Kecamatan Ngoro Kabupaten Jombang - Kartika Kurnia Eka Wardani; Yudi Krisno Wicaksono (Lembaga Pengembangan Kinerja Dosen, 2024)
Jombok Village is one of the villages that receives assistance from the Family Hope Program in Ngoro District, Jombang Regency, with a total of 245 families distributed every two months based on predetermined criteria. The majority of people's work is as farmers and traders because it suits the skills of the local community. Livelihood conditions with an uncertain amount of income each month make it difficult to fulfill daily living needs. So children prefer to work to help the family economy rather than continue higher education. With the help of the Family Hope Program (PKH) in the education sector, it is hoped that it will be able to increase the educational participation rate of poor children and this assistance is also expected to be able to reduce the burden on household expenses. These limitations make it more difficult for them to find better and more stable jobs, leading to dependence on social assistance. The aims of this research are (1) to determine the influence of the income level of the head of the family on the educational level of children receiving the Family Hope Program (PKH) in Jombok Village, Ngoro District, Jombang Regency, (2) to determine the influence of the Family Hope Program on the educational level of children receiving the Family Hope Program (PKH). ) in Jombok Village, Ngoro District, Jombang Regency. The method used in this research is a quantitative method with a descriptive approach. Data collection techniques use observation, questionnaires and documentation. The location of this research is Jombok Village, Ngoro District, Jombang Regency. The subjects in this research were recipients of the Family Hope Program (PKH) assistance who had dependent high school children. The data processing used in this research is validity testing, reliability testing, and classical assumption testing. The data analysis used in this research is multiple linear regression. The results of this research show that (1) The income level of the head of the family has a positive and significant effect on the education level of children receiving PKH in Jombok Village, Ngoro District, Jombang Regency, which can be proven by obtaining a value of t count > t table (3,265 > 1,666) and a significance value smaller than 5 % (0.002 < 0.05) (2) The Family Hope Program has a positive and significant effect on the education level of children receiving PKH in Jombok Village, Ngoro District, Jombang Regency which can be proven by obtaining a value of t count > t table (2.088 > 1.666) and a significance value of less than 5 % (0.041 < 0.05).